Friedrich Daniel Ernst Schleiermacher, Wybrane gorzowskie kazania/ Ausgewählte Landsberger Predigten, red./Hrsg. T. Kuźmicki, J. Dubiec- Stach, T. Kirchhof, Gorzów Wielkopolski 2024, ss. 237 - Froniewski, Jacek (Teologia w Polsce, 2024)
Recenzja książki: Friedrich Daniel Ernst Schleiermacher, Wybrane gorzowskie kazania/Ausgewählte Landsberger Predigten, red./Hrsg. T. Kuźmicki, J. Dubiec-Stach, T. Kirchhof, Gorzów Wielkopolski 2024, ss. 237